A Multicultural Personal Growth Group as a Pedagogical Strategy with Graduate Counseling Students - Jennifer Johnson; Glenn Lambie (Journal of the Scholarship of Teaching and Learning, 2012)
The present study investigated a six-week multicultural personal growth group as a pedagogical strategy to support first-year graduate counseling students’ (N = 20) levels of ethnic identity development (Phinney & Ong, 2007) and social-cognitive maturity (Hy & Loevinger, 1996). Students’ levels of ethnic identity and social-cognitive development did not change; however, 90% (n = 18) of the students reported valuing the group experience and appreciated the group leaders facilitation of the pedagogical strategy. Implications for the scholarship of teaching and learning are discussed.